2001
DOI: 10.1111/j.1478-4408.2001.tb00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of lightness difference formulae

Abstract: There are large variations between different previously published lightness difference experimental data sets. Two hundred and eight pairs of matt and glossy paint samples exhibiting mainly lightness differences were accumulated. Each pair was assessed about twenty times by a panel of fourteen observers using the grey scale method. The results were used to derive a new lightness difference formula (CII), and to a large extent, a possible new CIE lightness difference formula (CMC99). Both formulae were found to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…3,4 Recent experimental results showed that the L* scale gives too large DL* values for lightness differences both for dark and for light samples. 27 Therefore, in CIEDE2000, lightness is corrected with a specific weighting function (S L ). However, our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 Recent experimental results showed that the L* scale gives too large DL* values for lightness differences both for dark and for light samples. 27 Therefore, in CIEDE2000, lightness is corrected with a specific weighting function (S L ). However, our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While most of the datasets employed here covered wide regions of colour space, the two NCSU datasets analysed only very specific regions: low saturated blue [33] and black [34]. Among these viewing conditions, we include the material of the samples (related to its texture), because it may play a role in the optimal S L function [18,21] we are looking for, and also the lightness of the background, because it is necessary information to calculate Whittle's formula [37]. In addition, Table 2 provides information on the main viewing conditions for each of the 13 visual datasets.…”
Section: Experimental Datasets and Methodsmentioning
confidence: 99%
“…It was observed (Chou et al ., 2001) that perceived lightness difference is smallest for the darkest and lightest sample pairs, and the largest difference occurs for L * of 50. These results are consistent with the majority of the earlier work in that Δ E / Δ V (instrumental/visual perceptible difference) clearly increases as L * increases from L * = 50.…”
Section: Ciede2000 Colour-difference Formulamentioning
confidence: 77%